Pelatihan dan Pendampingan Pendidikan Karakter Keluarga Pada Posbakum Atiyatul Aisyiyah Daerah Kabupaten Pasaman - Nasrul, Wedy; Rahmi, Rahmi; Julhadi, Julhadi; Puadi, M; Rahmadani, Reza (Jurnal Pengabdian UntukMu NegeRI, 2025)
One of the factors contributing to domestic violence against children is the low level of character education among family members. Low character education results in a lack of empathy, immorality, and high levels of emotion among family members, leading to violence against children. The high number of child abuse cases in Pasaman Regency has prompted local community organizations to seek various solutions to reduce it. Aisyiyah Pasaman Regency is a women's organization that has long been concerned about children. However, the role of Aisyiyah Pasaman Regency in cases of child abuse has not been very visible. This activity aims to increase the knowledge of the Posbakum institution and Aisyiyah administrators regarding character education. The activity methods consisted of training and mentoring. The results of the training and mentoring showed an increase in the knowledge of Posbakum and Aisyiyah administrators regarding character education, enabling them to implement it in the community. The leaders and members of Posbakum and Aisyiyah were able to explain and instill character education in family members in their respective areas, thereby preventing violence against children.